Dolje s maskama - Petricic, Mladen (Croatia : Factum, 1999)
A simple but vivid documentary about an initiative on February 20th 1998 to hold a union strike on the main square of Zagreb. The aim of the film was to depict reactions of common people, avoiding the typical style of the TV documentaries at the time, which were mainly focused upon the conflict between demonstrators and police.
Duration: 00:27:00
Keywords: Documentary films